Learning to remember the Shoah - human rights education and prevention of anti-Semitism - Wilhelm Schwendemann (Studia z Teorii Wychowania)
Anti-Semitism and group hostility undermine coexistence in a democratic civil soci-ety. That is why the prevention of anti-Semitism, Islamophobia and xenophobia is one of the educational tasks of schools, but also of religious education in particular. In religious educa-tion, therefore, the concept of learning to learn about and after Auschwitz must be combined with a stringent model of human rights education, which brings with it new didactic chal-lenges.